Economics of Energy Conservation: A Case Study - Herath Gunatilake; Dhammika Padmakanthi (Asian Development Bank (ADB), 2008)
Global energy security relies heavily on exhaustible fossil fuels, whose use contributes significantly to global environmental problems. The recent unprecedented rise in oil prices and the threat of global warming highlight the urgent need for solutions to the energy and environment problem. Shifting to clean renewable energy sources - the long-term solution - has been slow despite efforts of the global community since the 1970s. Demand side management (DSM) is part of the solution to the energy crisis. Among DSM measures, energy conservation has greater potential in developing countries. This paper examines the financial and economic feasibility of adoption of an energy-conserving technology in the household sector in Sri Lanka. Results show that the adoption of this energy-conserving technology is financially profitable and economically viable. Systematic incorporation of environmental benefits further strengthens the case for energy conservation. The paper also discusses policy measures to solve low voluntary adoption, affordability issues, and information failures related to energy conservation.
hdl:11540/1782
Keywords: 330; Energieeinsparung; Technologiewahl; Elektrizitätswirtschaft; Förderung erneuerbarer Energien; Sri Lanka